2019
DOI: 10.1002/acr.23600
|View full text |Cite
|
Sign up to set email alerts
|

Patient Concerns and Perceptions Regarding Biologic Therapies in Ankylosing Spondylitis: Insights From a Large‐Scale Survey of Social Media Platforms

Abstract: Social media reveals a dynamic range of themes governing AS patients' experience and choice with biologics. The complexity of selecting among biologics and navigating their risk-benefit profiles suggests merit in creating online tailored decision-tools to support patients' decision-making with AS biologic therapies. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…Patients tend to be hopeful, but they have mixed feelings about bDMARDs, including a sense of anxiety and hopelessness ( 23 ). In an analysis of AS patient discussions on social media, patients voiced uncertainty about starting or continuing bDMARD therapy, and the uncertainty manifested chiefly in their numerous questions about it, especially their worries about its long‐term effectiveness ( 24 ). The cross‐sectional study presented here asked only about immediate symptoms or symptoms at the time a decision was made rather than longer‐term symptoms, but it was notable that prevention of long‐term consequences/damage was more important to bDMARD participants, compared with participants not on bDMARDs, than were current symptoms (ie, “how good or bad the disease is making me feel at the time of a treatment decision”).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients tend to be hopeful, but they have mixed feelings about bDMARDs, including a sense of anxiety and hopelessness ( 23 ). In an analysis of AS patient discussions on social media, patients voiced uncertainty about starting or continuing bDMARD therapy, and the uncertainty manifested chiefly in their numerous questions about it, especially their worries about its long‐term effectiveness ( 24 ). The cross‐sectional study presented here asked only about immediate symptoms or symptoms at the time a decision was made rather than longer‐term symptoms, but it was notable that prevention of long‐term consequences/damage was more important to bDMARD participants, compared with participants not on bDMARDs, than were current symptoms (ie, “how good or bad the disease is making me feel at the time of a treatment decision”).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study are part of an online registry and patient community and may be more likely to take part regularly in research studies and thus may have had greater interest in managing their disease, giving rise to the potential for selection bias. In the social media study reporting axSpA patient attitudes about TNFi treatment, patients had expressed a lack of trust in physicians and a need for psychological and social support, namely, an understanding from others in their social circle of what it is like to live in a body affected by the disease ( 24 ). In our study, participants largely expressed trust in their physician and considered the physician's guidance to be important in their treatment change decision.…”
Section: Discussionmentioning
confidence: 99%
“…To supplement the manual inductive coding process, we applied a second, more novel technique, LDA, that allowed for the review of the entire data set. LDA is an unsupervised probabilistic topic model process that relies on the contextual co-occurrence of words to identify patterns of words that, when found together, have a semantic meaning [11,12]. For example, the word "bank" can have different meanings when paired with "money" versus "water."…”
Section: Lda: a Quantitative And Qualitative Approachmentioning
confidence: 99%
“…14 One particular unsupervised topic modelling method, latent Dirichlet allocation (LDA), 15 has proven particularly popular and successful. LDA has been used for topic mining in studies of health data across an array of data sources, including discussions from condition-specific online support groups [16][17][18][19][20] and more general online discussion platforms, [21][22][23][24][25][26][27][28][29] data about adverse medical events, 30 interview transcripts of patients, 31 32 media articles 33 and survey data. 34 35 Other studies have used LDA to analyse topics in patient-reported concerns as well, in situations where no existing topic information is available.…”
Section: What Does This Paper Add?mentioning
confidence: 99%